2005
DOI: 10.1080/03637750500120485
|View full text |Cite
|
Sign up to set email alerts
|

Techne or Artful Science and the Genre of Case Presentations in Healthcare Settings

Abstract: This paper presents a qualitative study that investigated the role of case presentations in the socialization of medical and optometry students. Using the debate from classical rhetoric around the term techne (art or science), we observed that genre theory helps explain the way case presentations mediate the development of professional identity through the interaction of certain knowledge (techne 1), "savvy" knowledge (techne 2), and ethical reflection (phronesis). We noted that these mediated scenes of learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…Of note is the student's candor about his uncertainty with his supervisor who will ultimately evaluate him. This candor contrasts sharply with results from our earlier study of medical students performing case presentations (Lingard et al 2003a;Schryer et al 2005).…”
Section: Introductioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Of note is the student's candor about his uncertainty with his supervisor who will ultimately evaluate him. This candor contrasts sharply with results from our earlier study of medical students performing case presentations (Lingard et al 2003a;Schryer et al 2005).…”
Section: Introductioncontrasting
confidence: 84%
“…The attitudes toward clinical uncertainty displayed by these optometry students were consistent with those displayed in interviews with medical students in our earlier study (Lingard et al 2003a;Schryer et al 2005). Students in optometry and medicine consider clinical uncertainty in the case presentation to be dangerous and something that should be avoided if at all possible.…”
Section: 'Well It Wouldn't Be-i Don't Think It Would Be [Disease X]' supporting
confidence: 73%
See 1 more Smart Citation
“…We have found that the novice case presentation-during which patient information is presented by students to their instructors-is a complex discursive process, interwoven with the intentions of caring for the immediate patient while attending to the process of teaching and learning (e.g., Lingard et al 2003a, b;Schryer et al 2003Schryer et al , 2005Schryer et al , 2007Spafford et al 2004Spafford et al , 2005Spafford et al , 2006aSpafford et al , b, 2007. Through this work, we have noted that the problems associated with the tension of this balancing act increase when patients face potentially serious threats to their health.…”
Section: Introductionmentioning
confidence: 97%
“…This articulation sets the stage for the communication activities that CID typically supports such as speaking, writing, and working in teams. Activities such as writing (e.g., Bazerman, 1988;Berkenkotter & Huckin, 1995;Ding, 2008) and speaking (e.g., Dannels, 2000;Schryer, Lingard, & Spafford, 2005;Schryer & Spoel, 2005) represent vehicles for socialization into a discipline. These activities are also practices and spaces where social actors are saying and doing gender (Martin, 2003).…”
mentioning
confidence: 99%